The Relationship between Records Management and Service Delivery in Academic Libraries: A Case Study of Kabale University Library. - Forsca, Kyomugasho (Kabale University, 2019)
A research Report Submitted to the Faculty of Arts and Social Sciences in Partial Fulfillment of the Requirement for the Award of A diploma in Records Management of Kabale Univerity